EXPERIMENTAL INVESTIGATIONS OF A SOLAR PARABOLIC TROUGH COLLECTOR FOR CIRCULAR AND ELLIPTICAL ABSORBER - R, Suresh.; Bose.R, Subash Chandra; K, Arumugam.; R, Anbazhagan.; V, Sathiyamoorthy.; N.A, Nagendran.; E, Prakash. (JOURNAL OF ADVANCES IN CHEMISTRY, 2017)
Solar parabolic trough collector is one of the most efficient and an effective technology to deal with environmental pollution and it has gained much attention due to the recent energy demand. The solar parabolic trough collector is one of the most promising techniques for absorbing the heat from the sun. This heat is utilized for electricity generation and other industrial heating applications. This paper describes the theoretical and experimental assessment of performance of the circular and elliptical absorbers used in solar parabolic trough collector. The absorber tube of parabolic trough collector is used to transfer the heat to the working fluid. The working fluid considered over here is water which is the best operating medium in direct steam generation. The mass flow rate of water in absorber tube is analyzed in 3 stages as 0.016, 0.024 and 0.030 kg/s respectively. The experimental test is done in Chennai-Tamilnadu, Southern part of India which experiences a superior temperature throughout the year. The experiment is conducted for the period of one year from June 2015 to May 2016. The performance improvement focuses on collector efficiency, useful heat transfer rate, outlet temperature of working fluid, temperature gradient, overall heat transfer rate and the thermal losses.